The Effect Of Lemongrass Stem Infusion (Cymbopogon citratus) On Growth Of Streptococcus mutans - Azzadian Octa Kusuma; Endang Sri Lestari; Tyas Prihatiningsih; Nadia Hardini (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Objectives: To determine the effect of lemongrass infusion on the growth of Streptococcus mutans at various concentrations. Methods: This study used post test only control group design with total sample is 9 samples, concentration 100%, 50%, 25%, 12,5%, 6,25%, 3,125%, 1,56%, positive control, and negative control with 3 replications. The research uses dilution method by looking at the turbidity which can be marked as MIC, for MBC used pour plate method was determined by looking at the presence or absence of bacterial growth on the plate. Data analysis was performed using the spss application using Kruskal-Wallis test with significance level if the result of p<0,05. Results of Study: The results of the sample group were 100%, 50%, 25%, 12,5%, 6,25%, 3,125%, 1,56% in the MIC test showed turbidity in all samples, then the MBC test showed growth bacteria in all samples. The assessment of the probability test p value of 1,000 (>0,05) indicates that there is no significant difference between research groups. Conclusion: There was no effect of lemongrass stem infusion with various concentrations on the growth of Streptococcus mutans.